Micro and Macro Philosophy: Organicism in Biology, Philosophy, and Politics - Botz-Bornstein, Thorsten, (Value Inquiry Book Series ;, 2021)
What role can philosophy play in a world dominated by neoliberalism and globalization? Must it join universalist ideologies as it did in past centuries? Or might it turn to ethnophilosophy and postmodern fragmentation? Micro and Macro Philosophy argues that universalist cosmopolitanism and egocentric culturalism are not the only alternatives. Western philosophy has created a false dichotomy. A better solution can be found in an organic philosophy that functions through micro-macro interactions. According to biologists, the twentieth century was the century of the gene, while the twenty-first century is destined to be the century of the organic. Micro and Macro Philosophy attempts to establish such a view in philosophy: by highlighting micro-macro patterns found in history, it seeks to design new ways of "organic thinking" in the human sciences.